Novel method for the synthesis of siloxane nanowires and filaments using gold nanoparticle catalysts - Bhagavatula L. V. Prasad; Stoeva, S.; Sorensen, C. M.; Klabunde, Kenneth J.; Zaikovskii, V. (International Conference on Nanoscience and Technology, 2005)
A unique polymerization reaction of alkylsilanes to siloxane nanowires, filaments and tubes in presence of gold nanoparticles and water is presented. The gold nanoparticles, which catalyze this reaction also work as templates restricting the shape of the resulting polymers into wires and tubes. High resolution transmission electron microscopy images clearly reveal the presence of gold nanoparticle at the tip of each wire supporting the template hypothesis. Elemental analyses by different methods confirm the stoichiometry to be C18H37SiO1.5, when the alkylsilane used was C18H37SiH3, thus proving that the alkyl group remains intact during the polymerization reaction.
Keywords: gold nanoparticles; Nanowires; siloxane polymers